Skin cooling maintains cerebral blood flow velocity and orthostatic tolerance during tilting in heated humans - Wilson, Thad E; Cui, Jian; Zhang, Rong; Witkowski, Sarah; Crandall, Craig G (Journal of applied physiology (1985), 2002)
1  Institute for Exercise and Environmental Medicine, Presbyterian Hospital of Dallas, Dallas 75321; and 2  Department of Internal Medicine, University of Texas Southwestern Medical Center, Dallas, Texas 75235 Orthostatic tolerance is reduced in the heat-stressed human. The purpose of this project was to identify whether skin-surface cooling improves orthostatic tolerance. Nine subjects were exposed to 10 min of 60° head-up tilting in each of four conditions: normothermia (NT-tilt), heat stress (HT-tilt), normothermia plus skin-surface cooling 1 min before and throughout tilting (NT-tilt cool ), and heat stress plus skin-surface cooling 1 min before and throughout tilting (HT-tilt cool ). Heating and cooling were accomplished by perfusing 46 and 15°C water, respectively, though a tube-lined suit worn by each subject. During HT-tilt, four of nine subjects developed presyncopal symptoms resulting in the termination of the tilt test. In contrast, no subject experienced presyncopal symptoms during NT-tilt, NT-tilt cool , or HT-tilt cool . During the HT-tilt procedure, mean arterial blood pressure (MAP) and cerebral blood flow velocity (CBFV) decreased. However, during HT-tilt cool , MAP, total peripheral resistance, and CBFV were significantly greater relative to HT-tilt (all P  < 0.01). No differences were observed in calculated cerebral vascular resistance between the four conditions. These data suggest that skin-surface cooling prevents the fall in CBFV during upright tilting and improves orthostatic tolerance, presumably via maintenance of MAP. Hence, skin-surface cooling may be a potent countermeasure to protect against orthostatic intolerance observed in heat-stressed humans. hyperthermia; heat stress; syncope; transcranial Doppler